Prevalence of fibromyalgia in premenopausal and postmenopausal women and its relation to climacteric symptoms - Carranza-Lira, Sebastián; Villalobos Hernandez, Idun Berenice (Menopause Review/Przegląd Menopauzalny, 2014)
Aim of the study : To compare fibromyalgia prevalence in premenopausal and postmenopausal women and its relation to the climacteric symptoms. Material and methods : Two hundred and nine women were studied, who attended the gynecology consultation at the hospital. They were divided in two groups: group I (premenopausal, n = 113) and group II (postmenopausal, n = 96). In all of them, climacteric symptoms and fibromyalgia diagnostic criteria were investigated; for the latter, the evaluations were done according to the 1990 and 2010 criteria of the American College of Rheumatology. Results: When groups I and II were compared, no differences were found in somatometry, medicament consumption and associated diseases. When analyzing the general group, the fibromyalgia prevalence was greater in the postmenopausal women. However, when comparing the groups according to climacteric symptoms, in group I, 29% of symptomatic women had fibromyalgia, while only 4% of asymptomatic ones (p < 0.002). In group II, 15.7% of symptomatic women, and 2.5% of asymptomatic ones had fibromyalgia (p < 0.02). In group I, the more common painful points were the lower back (45.5%), neck (35.7%), and upper back (32.1%). The more frequent symptoms were non-restful sleep (49%), followed by fatigue and cognitive symptoms (42% for each one). In group II, the more common painful points were the lower back (42%), neck (40%) and upper back (38.5%). The more frequent symptoms were fatigue (69.6%), cognitive symptoms (59.3%) and non-restful sleep (57%). Conclusions : In premenopausal women, fibromyalgia was related to the presence of climacteric symptoms and in postmenopausal women – to their absence.